Surgical Correction of Different Severities of Astigmatism Using Wavefront-Optimized Photorefractive Keratectomy - Sharghi, Afshan; Ojaghi, Habib; Yavari, Saba; Zahirian Moghadam, Telma (International Journal of Psychosocial Rehabilitation, 2020)
Background and Objective: Astigmatism is a prevalent refractive error. One of the most common methods of refractive surgery is photorefractive keratectomy (PRK) surgery. The aim of this study is to determine the effectiveness of PRK on three types of astigmatism (mild, moderate, and severe).Methods: This prospective interventional case series was performed on 46 eyes of 25 patients with astigmatism ranging from 1 to 6 diopters with ≤1D sphere. After obtaining informed written consent, demographic information of patients and the results of the examination were recorded. The patients undergoing surgery were followed up for 12 months, and their data were then collected and statistically analyzed.Results: The mean preoperative and postoperative refractive astigmatism was -3.01±1.42 and -0.40±0.37 (D), respectively (p